Perceived social support and deviant behavior of new street corner youth on campus: a moderated mediation model - Chi, Hong; Fan, Linlin; Meng, Weijie (Frontiers in Psychology, 2024)
The current study aimed to examine the moderated mediation between perceived social support, deviant behavior of new street corner youth on campus, interpersonal needs (as a mediator), meaning in life (as a moderator). 596 new street corner youth on campus were investigated with Deviant Behavior Questionnaire, Perceived Social Support Scale, Interpersonal Need Questionnaire, and Meaning in Life Questionnaire. The findings showed that:(1) Perceived social support significantly and negatively predicted deviant behavior;(2) Interpersonal needs mediated the association between perceived social support and deviant behavior;(3) A moderated mediating role of perceived social support influencing deviant behavior was established, and the direct and the first half paths of the model were regulated meaning in life. The results have important value for deviant behavior of new street corner youth on campus.